Welcome to Westonci.ca, your one-stop destination for finding answers to all your questions. Join our expert community now! Get immediate and reliable answers to your questions from a community of experienced experts on our platform. Connect with a community of professionals ready to help you find accurate solutions to your questions quickly and efficiently.
Sagot :
y=mx+b
y=7 m=-5/4 x=-4 b=?
7=-5/4(-4)+b
7=5+b
7-5=5-5+b
b=2
Therefore, the equation is y=-5/4x+2
That's it.
y - y₁ = m(x - x₁)
y - 7 = -1¹/₄(x - (-4))
y - 7 = -1¹/₄(x + 4)
y - 7 = -1¹/₄(x) - 1¹/₄(4)
y - 7 = -1¹/₄x - 5
+ 7 + 7
y = -1¹/₄x + 2
y - 7 = -1¹/₄(x - (-4))
y - 7 = -1¹/₄(x + 4)
y - 7 = -1¹/₄(x) - 1¹/₄(4)
y - 7 = -1¹/₄x - 5
+ 7 + 7
y = -1¹/₄x + 2
We hope this was helpful. Please come back whenever you need more information or answers to your queries. We hope you found this helpful. Feel free to come back anytime for more accurate answers and updated information. Keep exploring Westonci.ca for more insightful answers to your questions. We're here to help.